It’s Not Easy Being Green: Behavior, Morphology, and Population Structure in Urban and Natural Populations of Green Anole (Anolis carolinensis) Lizards - Lailvaux, Simon P. (Frontiers in Ecology and Evolution, 2020)
Selection on behaviour, signalling, and morphology can be strongly affected by variation in habitat type. Consequently, populations inhabiting different environments can exhibit divergent phenotypes as a result of either habitat-specific selection or plasticity. Urban habitats in particular represent different challenges for organisms adapted for rural environments, including disparate complements of predators and competitors, resource availability, and habitat complexity. In this paper, I review work aimed at understanding the different selective challenges experienced by rural and urban populations of green anole lizards, primarily those in southeastern Louisiana. I also describe a long-term mark-recapture experiment on an urban population of green anoles in New Orleans, and consider how sex ratios and population density changes over time. Collectively, this work shows that urban and rural populations of green anoles diverge markedly in behaviour and morphology driven both by differences in habitat and the presence of competitors in the urban environment; however, it also shows that the effects of urbanization on the ecology and evolution of green anoles are understudied.